Physical properties, dietary fibre profile and peroxide value of biscuit produced from wheat-Tigernut flours with avocado paste as fat substitute - Onwuzuruike, Uzochukwu Anselm; P, Ukegbu; NE, Obasi; M, Ogah; I, Okereke; P.C, Uche; C, Echendu (Indonesian Food Science and Technology Journal, 2023)
This study investigated the effect of replacing fat with avocado paste on the physical properties, dietary fibre profile and peroxide value of wheat-tigernut biscuits. Whole tigernut was processed into flour and blended with wheat flour at three different levels; 10%, 20% and 30% weight basis into two parts. The first part of the composite (T10, T20, and T30) and control sample (100% wheat flour, T00) were baked into biscuit using margarine, while in the second batch (AT10, AT20, and AT30), margarine was replaced with avocado paste (100%). The biscuit samples were analysed for physical properties, dietary fibre profile and peroxide value using standard procedures. Data were subjected to Analysis of variance, and means were separated using Duncan’s Multiple Range Test at p<0.05. Biscuits baked with avocado paste had higher spread ratio (6.98 – 7.19) and weight (17.39 – 17.51 g) than samples baked with margarine. Break strength of control sample was higher (185g) compared to biscuit samples baked with margarine (182.70 – 175.81 g), but lower than biscuits baked with avocado paste (182.70 – 175.81 g). Biscuits baked with avocado had higher dietary fibre profile of 7.49 to 7.84% and 5.72 to 5.82% for insoluble and soluble fibres. Biscuits containing avocado paste had higher peroxide values (1.91 to 2.56 meq O2/kg) than samples containing margarine (1.67 to 2.18 meq O2/kg). Replacing avocado with margarine improved the physical properties and dietary fibre profile of the biscuits with no adverse effect on the peroxide value and could therefore, be exploited as a healthier shortening agent to enrich biscuits.